2015
DOI: 10.1016/j.cgh.2014.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Suspected Nonalcoholic Fatty Liver Disease in Hispanic/Latino Individuals Differs by Heritage

Abstract: Background & Aims Non-alcoholic fatty liver disease (NAFLD) was shown to disproportionally affect Hispanic persons. We examined the prevalence of suspected NAFLD in Hispanic/Latino persons with diverse backgrounds. Methods We studied the prevalence of suspected NAFLD among 12,133 persons included in The Hispanic Community Health Study/Study of Latinos. We collected data on levels of aminotransferase, metabolic syndrome (defined by National Cholesterol Education Program-Adult Treatment Panel III guidelines), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
81
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 28 publications
7
81
3
1
Order By: Relevance
“…As in previously published NHANES-based analyses of NAFLD, ultrasounds showing moderate or severe hepatic steatosis were classified as NAFLD and ultrasounds showing no or mild hepatic steatosis were classified as non-NAFLD (6). Consistent with previously published population-based analyses of NAFLD, aminotransferase thresholds used to identify NAFLD were: AST > 37 or ALT > 40 U/L in males or AST or ALT > 31 U/L in females (2). …”
Section: Dear Editorsupporting
confidence: 65%
See 1 more Smart Citation
“…As in previously published NHANES-based analyses of NAFLD, ultrasounds showing moderate or severe hepatic steatosis were classified as NAFLD and ultrasounds showing no or mild hepatic steatosis were classified as non-NAFLD (6). Consistent with previously published population-based analyses of NAFLD, aminotransferase thresholds used to identify NAFLD were: AST > 37 or ALT > 40 U/L in males or AST or ALT > 31 U/L in females (2). …”
Section: Dear Editorsupporting
confidence: 65%
“…We read with interest recent publications in Clinical Gastroenterology and Hepatology highlighting the high burden of nonalcoholic fatty liver disease (NAFLD) among Hispanics in the United States (1), as well as the variability in prevalence among Hispanics according to their heritage (2). NAFLD occurs as the consequence of a complex interplay of genetic, environmental, and lifestyle factors.…”
Section: Dear Editormentioning
confidence: 99%
“…The prevalence of NAFLD is also related to socioeco nomic factors, but their exact role is debated. In a study exploring the role of environmental factors in different ethnic groups with NAFLD, acculturation, education level, health care use and income, along with dietary and lifestyle factors and sleep, were not found to be indepen dently associated with risk of developing NAFLD, suggest ing that environmental factors might have a role on a background of genetic predisposition 16 .…”
Section: Risk Factors: Nature or Nurture?mentioning
confidence: 99%
“…Specifically, NAFLD prevalence (assessed by ultrasonography) for South America has been estimated to be ~30.45% (95% CI 22.74-39.4%) 1 . The majority of studies reporting the preva lence of NAFLD from South America have been performed in Brazil [15][16][17] . Nevertheless, in a study reported from Chile, the prevalence of NAFLD (diagnosed using…”
mentioning
confidence: 99%
“…6 Among the Hispanic population, those of Mexican heritage have the highest prevalence while Dominican Republicans have the lowest prevalence. 7, 8 The etiology of this racial and ethnic disparity is likely multi-factorial and includes contributions from genetic, behavioral and socio-economic factors. 9 …”
Section: Introductionmentioning
confidence: 99%